Prevalence of generalized anxiety disorder and major depression in health-care givers of disabled patients in Majmaah and Shaqra cities, Kingdom of Saudi Arabia - Alzahrani, Mansour; Alfahaid, Fahad; Almansour, Mohammed; Alghamdi, Talal; Ansari, Tahir; Sami, Waqas; Al Otaibi, Talal Mislat; Al Humayn, Abdulmohsen Abdullah; Al Enezi, Madullah Moutlaq (International Journal of Health Sciences, 2017)
Introduction: Anxiety is an emotion characterized by feelings of tension, worried thoughts, and physical changes such as increased blood pressure, etc. The impact of anxiety and depression on health-caregivers of disabled patients are very important because these psychological disorders effects both the health-caregivers and the patients which lead to unexpected bad events. Objectives: The current study was aimed to find out the prevalence of generalized anxiety disorder and major depression in health-care givers of disabled patients and to observe associations between demographic characteristics and psychological disorders in Majmaah and Shaqra Cities, Kingdom of Saudi Arabia. Methods: A cross-sectional community-based study was conducted in rehabilitation centers at Majmaah and Shaqra Cities. The data comprising 100 health-care givers was collected from February to April 2015 through complete enumeration sampling method. A pre-validated “general health quality questionnaire” was used to collect the data. Results: Majority of the participants were male (n = 75, 75%). More than 50% of the participants were holding bachelors’ degree. Almost three-fifths of the participants had monthly income between 5000 and 15,000 SAR. The prevalence of somatic disorder was only (2%), anxiety disorder (3%), and depression (1%). However, in psychosocial and stress, the prevalence was (8%), respectively. No significant association was observed between demographic characteristics (nationality, gender, marital status, educational level, occupation, and income) and psychological disorders (somatic, anxiety, psychosocial, depression, and stress) P > 0.05, respectively. Conclusion: The prevalence of psychological disorders was very low. Nationality, gender, marital status, educational level, occupation, and income were not significantly associated with psychological disorders.